'Stupid and lazy' youths? Meritocratic discourse and perceptions of popular stereotyping of VET students in China. Issue 4 (4th July 2022) - Wang, Geng
ABSTRACT: Since the start of the Reform Era in 1978, vocational education and training (VET) in China has been seen as inferior to academic routes and positioned at the bottom of the educational hierarchy. VET students are stereotyped as being 'stupid and lazy' and suffer considerable prejudice in Chinese society. Drawing on Foucault's disciplinary power and Ball's idea of performativity, this paper analyses how academically focused, exam-driven societal attitudes, as a form of meritocratic discourse, impact on these students and on how they perceive their stereotyped position within the Reform Era educational system. The findings reveal that these students have internalised the ideology of meritocracy, coming to see themselves as inferior and inadequate compared to their academic counterparts. Turning 'the gaze' upon themselves, they examine whether they 'add up' and assume responsibility for their own 'failures'. VET students are trained to be the new kind of youthful subject required to sustain the Reform Era China's engagement with neoliberal governance.